2013
DOI: 10.1002/art.37986
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Epigenome Modifiers, Including Aurora Kinases A and B, in Immune Cells in Rheumatoid Arthritis in Humans and Mouse Models

Abstract: Objective The aim of this study was to identify epigenetic factors that are implicated in the pathogenesis of rheumatoid arthritis (RA) and to explore the therapeutic potential of the targeted inhibition of these factors. Methods PCR arrays were utilized to investigate the expression profile of genes that encod key epigenetic regulator enzymes. Mononuclear cells from RA patients and mice were monitored for gene expression changes, in association with arthritis development in murine models of RA. Selected gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…13,14 Taken together, these studies suggest that epigenetic aberrations can cause and certainly mediate autoimmune disease progression. 15 Recently, a study on epigenetic alterations in PBMCs of RA patients was conducted by Glant et al 16 They showed that epigenome modifiers are differentially expressed in RA versus control patients. Unfortunately, in the study by Glant et al, the expression of histone variants was not examined.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Taken together, these studies suggest that epigenetic aberrations can cause and certainly mediate autoimmune disease progression. 15 Recently, a study on epigenetic alterations in PBMCs of RA patients was conducted by Glant et al 16 They showed that epigenome modifiers are differentially expressed in RA versus control patients. Unfortunately, in the study by Glant et al, the expression of histone variants was not examined.…”
Section: Introductionmentioning
confidence: 99%
“…Our group performed the first study on arthritis-related epigenetic modifiers [20], in which chromatin-modifying enzymes were analyzed in B and T cells from arthritic mice and peripheral blood mononuclear cells from patients with RA. All chromatin-modifying enzyme families were represented in the repertoire of genes with arthritis-specific expression, including histone kinases, acetyltransferases, deacetylases, methyltransferases and demethylases, as well as ubiquitin ligases.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated elevated aurora kinase A and B expression in arthritis, which was correlated to promotion of T-cell proliferation via increased histone H3 phosphorylation. This latter study also found increased B-cell apoptosis following treatment with a pan-aurora kinase inhibitor (VX680) [195].…”
Section: Other Inhibitors That Have Targets Outside the Mapk Or Pi3k mentioning
confidence: 92%